Civil Liability Insurance for Users of Personal Transport Equipment (PTE) as an Element of Protection for Sharing Economy Participants - Laskowska, Iwona; Wieteska, Stanisław; Juszczyk, Sławomir (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: In recent years, there has been a noticeable and dynamic development of micromobile equipment intended for the transport of people. These types of vehicles are known as personal transport equipment (PTE). Like any road vehicle, PTE can also cause numerous accidents and collisions. A natural consequence of damage related to the use of PTE is posing the question about securing the interests of the aggrieved parties. Considering the above, the aim of this paper is to present the role of civil liability insurance for users of personal transport equipment in the context of claims related to the use of this type of vehicles and to provide a brief description of insurance products available on the market. The paper presents the following thesis: although the regulations do not oblige PTE users to have a civil liability insurance policy, a wide catalogue of adverse events related to the PTE use requires the popularisation of insurance protection for users of this type of vehicles. Such insurance protection should cover: equipment users, renters, sellers, and operators, as well as households. Methodology: The paper is theoretical and analytical in its nature. In addition to the review of the available literature, the existing offer of voluntary insurance for PTE users is also analysed. Results of the research: Insurance addressed to users of personal transport equipment is a relatively new product on the market and still few insurance companies have it in their offer. PTE users can utilise their civil liability insurance often being part of their home insurance in their private life, which offers protection in the event of damage to third parties. One of the solutions leading to the dissemination of insurance protection could be a proposal of insurance tailored to the type of risk and short-term use associated with this kind of equipment (e.g. travel-type insurance).